Early childhood anaemia more than doubles the risk of developmental vulnerability at school‐age among Aboriginal and Torres Strait Islander children of remote Far North Queensland: Findings of a retrospective cohort study. Issue 3 (8th January 2020) - Leonard, Dympna; Buettner, Petra; Thompson, Fintan; Makrides, Maria; McDermott, Robyn
Abstract: Aims: Early childhood anaemia, usually attributed to iron deficiency, is associated with persistent detrimental effects on child development. This study investigates the association of anaemia between age six and 23 months with indicators of childhood development at school‐age among children of remote Aboriginal and Torres Strait Islander communities of Far North Queensland. Methods: The triennial Australian Early Development Census (AEDC) encompasses five domains of early childhood development—physical health and wellbeing, social competence, emotional maturity, language and cognitive skills (school‐based), communication skills and general knowledge. AEDC 2012 and 2015 assessments were linked with health information for children and their mothers from remote Aboriginal and Torres Strait Islander communities of Far North Queensland. Results: AEDC assessments were available for 250 children who had measurements of haemoglobin recorded at age 6 to 23 months. More children who had had early childhood anaemia (n = 66/143, 46.2%, [37.9%, 54.4%]) were developmentally vulnerable on two or more domains compared to those who had not been anaemic (n = 25/107, 23.4% [15.2%, 31.5%], P  < .001). Multivariable analysis confirmed that early childhood anaemia more than doubled the risk of developmental vulnerability (OR 2.2 [1.1, 4.3] P = .020) at school age. Conclusions: Early childhood anaemia is a risk factor for developmental vulnerability at school‐age in this setting. Interventions combining nutrition promotion and multi‐micronutrient food fortification, are effective in prevention of early childhood anaemia. Such interventions could also improve early childhood development and subsequent educational achievement.